2008
DOI: 10.1038/nature07449
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Myc oncogenic activity by ribosomal protein haploinsufficiency

Abstract: The Myc oncogene regulates the expression of multiple components of the protein synthetic machinery, including ribosomal proteins, initiation factors of translation, Pol III, and rDNA1,2. An outstanding question is whether and how increasing the cellular protein synthesis capacity can affect the multi-step process leading to cancer. We utilized ribosomal protein heterozygote mice as a genetic tool to restore increased protein synthesis in Eμ–Myc/+ transgenic mice to normal levels and show that in this context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
404
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(427 citation statements)
references
References 34 publications
21
404
1
1
Order By: Relevance
“…However, p53 induction was abolished by knockdown of c-Myc, indicating that c-Myc activity is necessary to stabilize p53 protein. Interestingly, recent studies have shown that ribosomal protein haploinsufficiency suppresses the activity of c-Myc (Barna et al, 2008). In conjunction with our results, this suppression of c-Myc activity may be caused by reduced level of c-Myc.…”
Section: Discussionsupporting
confidence: 90%
“…However, p53 induction was abolished by knockdown of c-Myc, indicating that c-Myc activity is necessary to stabilize p53 protein. Interestingly, recent studies have shown that ribosomal protein haploinsufficiency suppresses the activity of c-Myc (Barna et al, 2008). In conjunction with our results, this suppression of c-Myc activity may be caused by reduced level of c-Myc.…”
Section: Discussionsupporting
confidence: 90%
“…However, our data indicate that PTBP1 have a positive effect on CKD11 p58 expression. Moreover, the previous report indicates that MYC might play an important role and positive effect on IRES-dependent translation (54). Further study might reveal this discrepancy.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, our studies on glioblastoma cell lines have shown a higher sensitivity of tumor cells against the inhibition of hypusine synthesis compared with normal human astrocytes (16), suggesting that certain malignant cells depend on an activated hypusinedependent translation that is above the activation level in normal cells. An intriguing observation made by using another tumor model is that haploinsufficiency of ribosomal proteins attenuates Myc-dependent malignant transformation without affecting normal cells (72). This clearly highlights the dependence of tumor cells on elevated translational activity.…”
Section: Discussionmentioning
confidence: 90%